Multi‐institutional analysis of recurrence and survival after hepatectomy for fibrolamellar carcinoma. Issue 4 (21st May 2014) - Groeschl, Ryan T.; Miura, John T.; Wong, Ray K.; Bloomston, Mark; Lidsky, Michael L.; Clary, Bryan M.; Martin, Robert C.G.; Belli, Giulio; Buell, Joseph F.; Gamblin, T. Clark
Abstract Background and Objectives Fibrolamellar carcinoma (FLC) presents in young, otherwise‐healthy individuals. This study examined recurrence and survival characteristics after surgical resection for FLC by utilizing an international multi‐institutional database. Methods Consecutive patients undergoing hepatectomy for FLC from six institutions (1993–2010) were reviewed retrospectively. Survival was studied with life tables and Cox regression models. Results Thirty‐five patients (13 female, 37%) were included (median age: 32 years). R0 resection was achieved in all curative‐intent operations (n = 30), and palliative operations were performed for five patients. Crude 30‐day morbidity and mortality rates were 22% and 3%, respectively. For curative‐intent surgery, overall and recurrence‐free survivals at 5 years were 62% and 45%, respectively. In patients who achieved a 4‐year disease‐free interval after surgery, none subsequently developed recurrence. In multivariate models, presence of extrahepatic disease was the only factor that independently predicted overall (hazard ratio [HR]: 5.58, 95% confidence interval [CI]: 1.38–22.55, P = 0.016) and recurrence‐free survival (HR: 5.64, 95% CI: 1.48–21.49, P = 0.011). Conclusions Patients with surgically amenable FLC had encouraging long‐term survival. Recurrence‐free survival to 4 years suggested possible freedom from disease thereafter. Recurrent resectable disease was associated with an excellent prognosis, and repeat surgery should be strongly considered. J. Surg. Oncol. 2014; 110:412–415. © 2014 Wiley Periodicals, Inc.